Economic booms or bubbles: new opportunities for sustainable growth - Álvarez Falcón, César (2012)
The sustainable economic growth of countries such as Peru should be an inevitable consequence of the efficient use of resources generated by the price differentials of its natural resources and primary goods, during periods of economic booms. To this end, it is important to discern between the concepts of economic Bubble and Bell in the uncertain panorama of the world economy. Finally, it is fundamental to point out that the Bells, in spite of being a valid model for the explanation of differences in economic activity, do not show the dynamic nature that reality presents, therefore this paper refers to a model of economic Bubbles, with a dynamic behavior to explain the economic activity of a country.